2018
DOI: 10.1111/jvh.12996
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus surveillance and identification of human pegivirus 2 in a large Cameroonian cohort

Abstract: The prevalence of chronic hepatitis C virus (HCV) and the presence of human pegivirus 2 (HPgV-2) have not been examined in Cameroon, although HCV has been associated with HPgV-2 infections previously. Herein we aimed to characterize the burden and genetic diversity of HCV and the presence of HPgV-2 in Cameroon. Retrospective plasma specimens collected from N = 12 369 consenting subjects in South Cameroon from 2013 to 2016 were included in the study. The majority (97.1%) of participants were patients seeking he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…HPgV, formerly called hepatitis G virus (HGV) [9] or GB virus type C (GBV-C) [1], and the second human pegivirus (HPgV-2) [10] or human hepegivirus-1 (HHpgV-1) [5]. HPgV-2 was first reported in the US in 2015 [5,10], and has since been documented in the UK, China, Vietnam, Cameroon, and Iran [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPgV, formerly called hepatitis G virus (HGV) [9] or GB virus type C (GBV-C) [1], and the second human pegivirus (HPgV-2) [10] or human hepegivirus-1 (HHpgV-1) [5]. HPgV-2 was first reported in the US in 2015 [5,10], and has since been documented in the UK, China, Vietnam, Cameroon, and Iran [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed a low prevalence of HPgV-2 viremia in the general population, and an increased prevalence in patients infected with hepatitis C virus (HCV) [10,12,13,15] as well as in people who inject drugs (PWID) and are co-infected with HCV and human immunodeficiency virus type one (HIV-1) [11,15,25,26]. These data show a strong association between HPgV-2 and HCV and especially HCV/ HIV-1 co-infection [10-13, 15, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, HPgV-2 has been documented in the USA, UK, China, Vietnam, Cameroon, Iran, etc. (Bonsall et al, 2016;Anh et al, 2018;Bijvand et al, 2018;Wang et al, 2018a;Rodgers et al, 2019). It is noteworthy that HPgV-2 is epidemiologically tightly associated with HCV infection (Berg et al, 2015;Anh et al, 2018;Kandathil et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Rodgers et al, 2019) and shares several common genomic features with HCV (Kapoor et al, 2015;Bonsall et al, 2016;Coller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(Bonsall et al, 2016;Anh et al, 2018;Bijvand et al, 2018;Wang et al, 2018a;Rodgers et al, 2019). It is noteworthy that HPgV-2 is epidemiologically tightly associated with HCV infection (Berg et al, 2015;Anh et al, 2018;Kandathil et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Rodgers et al, 2019) and shares several common genomic features with HCV (Kapoor et al, 2015;Bonsall et al, 2016;Coller et al, 2016). HCV is a genetically diverse RNA virus and has seven genotypes and 67 subtypes (Smith et al, 2014) due to high error rate of RNA polymerase during replication (Moradpour et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation